PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF DIGITAL SMART APPS CREATOR PADA MATERI PECAHAN KELAS IV DI SDS YOS SUDARSO MEDAN - Br Ginting, Greace Naomi (Jurnal Pendidikan Dasar, 2025)
This study examines the validity, practicality, and effectiveness of digital interactive learning media based on Smart Apps Creator for teaching fractions to fourth-grade students at SDS Yos Sudarso Medan. The media was developed using the R&D model with the ADDIE approach, consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. Validation by experts and practitioners categorized it as "highly feasible" with an average score of 89.33%. Its practicality reached 90%, indicating ease of use for teachers and students in the learning process. The media’s strength lies in its interactive features, which enhance student engagement and present fraction concepts through visually appealing animations. Additionally, this media is designed to be flexibly used in both online and offline learning environments. Its effectiveness was measured through an increase in pre-test scores (67%) to post-test scores (82.5%), with an N-Gain Score of 0.45 (moderate category). The results confirm that this learning media is valid, practical, and effective, with potential for further development in elementary mathematics education to optimize conceptual understanding.